DETERMINATION OF THE SITE AMPLIFICATION ON DEEP SOIL LAYER USING 1-D SITE RESPONSE ANALYSIS (CASE STUDY: JAKARTA CITY, INDONESIA) - Delfebriyadi, Delfebriyadi; Irsyam, Masyhur; Hutapea, Bigman M.; Imran, Iswandi; Asrurifak, Muhammad (ITB Journal Publisher, LPPM ITB, 2019)
The dynamic response of deep soil layers is used in the development of microzonation maps. The empirical correlation between standard penetratation blow count numbers and S-wave velocity was derived for practical purposes in site characterization based on local data in a case study in Jakarta, Indonesia. For estimating the intensity of potential earthquake shaking at the ground surface as a function of depth to the bedrock surface layer, 1-D site response analysis was carried out in 5745 simulations. The site amplification values were then evaluated by dividing the spectral acceleration (SA) at ground surface by the SA at rock outcrop. Plots of the SA amplification values at interested depth intervals of the bedrock surface layer were assigned. The results showed that the site amplification values estimated by considering the local depth of the bedrock surface layer were generally smaller than the SA amplification values from the Indonesian seismic building code SNI-1726-2012. Also, there appears to exist a tendency of lower levels of mean regression of amplification, in particular for the soft soil site class.